Thermal pressure swing adsorption (TPSA) system for the removal of carbon dioxide - Mulgundmath, Vinay (University of Ottawa (Canada), 2009)
Adsorption behaviour of various gases have been studied in this work for air pre-purification, landfill gas, coal gas, natural gas and flue gas applications. This study included physical adsorption of commonly found impurities in air like carbon dioxide, methane, ethylene, acetylene, nitrous oxide, acetonitrile, methyl tert-butyl ether, methyl sulfoxide, dimethyl sulfoxide and methanol which constitute a safety hazard in the cryogenic air separation plant when present even in small quantities. Henry's law constants and heat of adsorption values were determined using the concentration pulse chromatographic technique for pure and composite adsorbents. It was found that latter performed better for these separations. Single component and binary mixture adsorption isotherms were obtained using constant volume and concentration pulse chromatographic techniques for three gas separation applications: CH4-N2, CO2 -CH4 and CO2-N2. Experimental x-y diagrams and equilibrium separation factors determined showed that Ceca 13X is a promising adsorbent to preferably adsorb CO2 from N2 and CO 2 from CH4. A novel, lab scale two bed advanced dynamic adsorption analysis system was designed and built in-house. Ceca 13X was used in this system to study the temperature and concentration profiles in the column, for a composition of 10% CO2 (by vol) in N2 which represented dry flue gas. Column breakthrough experiments were performed to compare the Pressure Swing Adsorption (PSA) process with Thermal Pressure Swing Adsorption (TPSA) process for CO2 recovery. A novel and yet a simple approach was used to model the non-isothermal adsorption in the fixed bed which exhibited significant heat effects for this system. Also, effects of various operating parameters on the TPSA performance such as purge/feed flow ratio, purge temperature, purge time and column pressure were investigated to optimise the CO2 recovery. Results indicated that better regeneration conditions used in a TPSA cycle was essential over a PSA cycle for recovering the maximum adsorption capacity of the used 13X. The developed model indicated to be an adequate representation of the experimental data. It was also observed that purge time had the most significant effect on CO2 recovery.
Keywords: Engineering, Chemical.